The Fantasy-Adventure Films as Contemporary Epics, 2000-2007 - Campos, Patrick F. (Plaridel Journal of Communication, Media, and Society; Vol 6 No 1 (2009): Media and Folklore, 2011)
This paper aims to compare the narrative form and themes of the folk epic (as typified by Labaw Donggon) and the contemporary fantasy-adventure film (as typified by the four Enteng Kabisote films). Labaw Donggon, an epic from the Sulod society of Central Panay, possesses all the universally decipherable elements of the epic narrative. On the other hand, the Enteng Kabisote films' narrative forms, themes, social contexts, and function may be generalized as applicable to most, if not all, of the other fantasy-adventure films at the turn of the century. The four films are found to be episodic like ethnoepics as they have loosely connected episodes, adventurous detours, and skirmishes forestalling a final battle. The contemporary fantasy-adventure film is also found to be cyclical with its repetitions and recreations, novel retellings, sequels and prequels, and the addition of new episodes and characters. As typified by the Enteng Kabisote films, the contemporary fantasy-adventure film perpetuates a narrow, even muddled, sense of nation. It has shrunk its vision into the comfort zone of the family, insecure about and unsure of the individual's and the nation's abilities to aspire for heroism and expansion. Instead of expanding the oft-repeated centrallity of the family in the ethnoepic, the fantasy-adventure film has remained fixated on this theme and has neither widened, deepened, nor problematized it.